The Mexican Credit Reporting Industry Reform: A Case Study - Gil Hubert, Johanna (Washington, DC: World Bank, 2012)
A country's legal and regulatory framework for credit reporting and data protection has a significant impact on how, and even whether, a credit reporting industry develops. This case study describes Mexico's experience encouraging competition in the credit information market. It touches upon its key aspects, including the main drivers and objectives; the reform stages and constituents and institutions involved in them; obstacles faced and how they were overcome; results and outcomes of the reform; and some of the lessons learned.